PESISIR MENGAJAR: FOSTERING COMMUNITY AWARENESS THROUGH SCHOOL CHILDREN EDUCATION IN TANGERANG REGENCY - SM.A. Hari Mahardika; Jhowilyn Zaldivar (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2018)
The two main problems in Tangerang Regency are poverty and deterioration in the quality of the environment, to overcome this, Tangerang Regency develops and implements the Gerbang Mapan, one of its programs is the Pesisir Mengajar program. The aims at the program to increase public awareness through education and dissemination of information specifically in primary schools on coastal environmental conservation issues. Learning activities are aimed at providing a new atmosphere in the teaching and learning process of elementary schools in the coastal areas of Tangerang Regency. Until now, this program has been able to recruit 60 volunteers and reach 30 coastal elementary schools. The official slogan of the program is: